2008
DOI: 10.1177/0891988708328217
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Everyday Functional Abilities of Dementia Patients With the Mini-Mental State Examination

Abstract: The Mini-Mental State Exam (MMSE) is a widely used cognitive screening measure. The purpose of the present study was to assess how 5 specific clusters of MMSE items (i.e., subscores) correlate with and predict specific areas of daily functioning in patients with dementia. Sixty-one patients with varied forms of dementia were administered the MMSE and an observation-based daily functional test (the Direct Assessment of Functional Status; DAFS). The results revealed that the orientation and attention subscores o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 23 publications
2
21
2
Order By: Relevance
“…This finding diverges from previous studies that have indicated that the MMSE total score was linked with daily functioning (Warren et al, 1989) and predicted these skill-related constructs when other assessments were used (Ford et al, 1996;Gill et al, 1997;Royall et al, 2007;Razani et al, 2009).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This finding diverges from previous studies that have indicated that the MMSE total score was linked with daily functioning (Warren et al, 1989) and predicted these skill-related constructs when other assessments were used (Ford et al, 1996;Gill et al, 1997;Royall et al, 2007;Razani et al, 2009).…”
Section: Discussioncontrasting
confidence: 84%
“…Warren et al (1989) found a strong association between Instrumental Activities of Daily Living (IADL) and the MMSE. Razani et al (2009) determined that MMSE orientation and attention subscores were significantly correlated with most functional domains measured by the Direct Assessment of Functional Status (DAFS). The MMSE language items correlated with all functional tasks except the shopping and time orientation tasks, while its recall items correlated with the DAFS's time orientation and shopping tasks.…”
Section: Introductionmentioning
confidence: 99%
“…in these areas were regarded as a hallmark of early AlzheimerÕs disease. Moreover, it was suggested that the summed score of orientation-to-time and attention was a valid subscale for predicting the total MMSE score (52), and these domains were the greatest and most significantly correlated with daily functioning (53). Our results showed that the domains of orientation to time and attention were significantly associated with mortality.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, it was suggested that the summed score of orientation-to-time and attention was a valid subscale for predicting the total MMSE score (52), and these domains were the greatest and most significantly correlated with daily functioning (53). Moreover, it was suggested that the summed score of orientation-to-time and attention was a valid subscale for predicting the total MMSE score (52), and these domains were the greatest and most significantly correlated with daily functioning (53).…”
Section: Discussionmentioning
confidence: 99%
“…These findings demonstrate that neuropsychological tests to some degree predict daily functioning in patients with AD, and that certain domains of neuropsychological functioning are better suited for predicting overall daily functioning than others. Findings from other studies echo these results, and extend them by identifying specific clinical measures with the greatest utility for predicting real-world functioning (Razani, et al, 2007; Mitchell & Miller, 2008; Razani, et al, 2009). A better understanding of the relationship between specific neuropsychological measures and their associated functional correlates would help clinicians better predict the ecological impairments that patients are likely to face.…”
supporting
confidence: 55%